Deciphering the role of the two conserved motifs of the ECF41 family σ factor in the autoregulation of its own promoter in Azospirillum brasilense Sp245. Issue 11 (1st June 2022) - Pathak, Ekta; Dubey, Ashutosh Prakash; Singh, Vijay Shankar; Mishra, Rajeev; Tripathi, Anil Kumar
Abstract: In Azospirillum brasilense, an extra‐cytoplasmic function σ factor (RpoE10) shows the characteristic 119 amino acid long C‐terminal extension found in ECF41‐type σ factors, which possesses three conserved motifs (WLPEP, DGGGR, and NPDKV), one in the linker region between the σ 2 and σ 4, and the other two in the SnoaL_2 domain of the C‐terminal extension. Here, we have described the role of the two conserved motifs in the SnoaL_2 domain of RpoE10 in the inhibition and activation of its activity, respectively. Truncation of the distal part of the C‐terminal sequence of the RpoE10 (including NPDKV but excluding the DGGGR motif) results in its promoter's activation suggesting autoregulation. Further truncation of the C‐terminal sequence up to its proximal part, including NPDKV and DGGGR motif, abolished promoter activation. Replacement of NPDKV motif with NAAAV in RpoE10 increased its ability to activate its promoter, whereas replacement of DGGGR motif led to reduced promoter activation. We have explored the dynamic modulation of σ 2 ‐σ 4 domains and the relevant molecular interactions mediated by the two conserved motifs of the SnoaL2 domain using molecular dynamics simulation. The analysis enabled us to explain that the NPDKV motif located distally in the C‐terminus negatively impacts transcriptional activation. In contrast, the DGGGR motif found proximally of the C‐terminal extension is required to activate RpoE10.